2018
DOI: 10.3390/ijms19113696
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Xanthine Levels in Pregnancy Complicated by Gestational Diabetes Mellitus—The Effect on Adverse Pregnancy Outcomes

Abstract: Uric acid (UA) levels are associated with many diseases including those related to lifestyle. The aim of this study was to evaluate the influence of clinical and anthropometric parameters on UA and xanthine (X) levels during pregnancy and postpartum in women with physiological pregnancy and pregnancy complicated by gestational diabetes mellitus (GDM), and to evaluate their impact on adverse perinatal outcomes. A total of 143 participants were included. Analyte levels were determined by HPLC with ultraviolet de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…More than 50% of patients with hyperuricemia have obesity, 40%-49.7% of patients with hyperuricemia have hypertension, and 9.5%-13.5% of patients with hyperuricemia also have diabetes [5]. Recently, it was reported that high urate and xanthine levels even became one of the risks of gestational diabetes mellitus [6]. However, the mechanism by which hyperuricemia develops into gout and its effect on other metabolic disorders is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of patients with hyperuricemia have obesity, 40%-49.7% of patients with hyperuricemia have hypertension, and 9.5%-13.5% of patients with hyperuricemia also have diabetes [5]. Recently, it was reported that high urate and xanthine levels even became one of the risks of gestational diabetes mellitus [6]. However, the mechanism by which hyperuricemia develops into gout and its effect on other metabolic disorders is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In placenta, nobiletin down-regulated valine degradation associated proteins, while up-regulating xanthine and xanthosine salvage associated proteins. These findings are noteworthy, given the documented increased concentrations of valine [70] and xanthine [71] in GDM pregnancies. These data suggest that nobiletin may regulate placental nutrient metabolism in GDM mice.…”
Section: Discussionmentioning
confidence: 65%
“…Several purine degradation metabolites were upregulated in GDM up to the second trimester of pregnancy. Hypoxanthine was elevated in 2 prediagnosis studies [ 17 , 25 ] and in 1 unpublished postdiagnosis study (Heath, Phelan, La Frano; personal communication), xanthine was elevated in 2 prediagnosis studies [ 25 , 88 ] and in 1 at-diagnosis study [ 89 ], and uric acid increased between the first and second trimesters in a prediagnosis study [ 17 ]. Increased levels of xanthine in serum during early pregnancy may be predictive of GDM.…”
Section: Other Metabolic Pathways Alteredmentioning
confidence: 99%